1875 Cal. Stat. 628 - (:unkn) unknown (My University, 1875)
Allowed the city of San Jose to regulate the storage of gunpowder and other combustibles and explosive substances within the incorporated limits of the city.
Keywords: GUNPOWDER - STORAGE